2021
DOI: 10.3390/md19070360
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharide Alleviates Abnormal Glucose Metabolism without Inhibition of Hepatic Lipid Accumulation in a High-Fat Diet/Streptozotocin-Induced Diabetic Rat Model

Abstract: This study investigated the effects of chitosan oligosaccharide (COS) on glucose metabolism and hepatic steatosis in a high-fat (HF) diet/streptozotocin-induced diabetic rat model. Male Wistar rats were divided into: (1) normal control (NC group), (2) HF diet (HF group), (3) streptozotocin (STZ)-induced diabetes with HF diet (DF group), and DF group supplemented with (4) 0.5% COS (D0.5F group), (5) 1% COS (D1F group), and (6) 5% COS (D5F group) for 4 weeks. COS supplementation significantly decreased the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In this study, the fasting glucose levels in NC rats was 226.4 mg/dL, which seems a little bit too high in contrast to existing literature data. Nonetheless, the observation is consistent with our prior studies that the fasting glucose levels of control rats typically fell within 170~220 mg/dL range [ 30 , 31 , 46 ]. Moreover, the HOMA-IR value in DF group was slightly lower than in the DM group, however, there was no significant difference between the two groups, which was likely due to the fact that the fasting insulin levels did no differ between DM and DF groups, as HOMA-IR is calculated based on the fasting blood glucose and insulin levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the fasting glucose levels in NC rats was 226.4 mg/dL, which seems a little bit too high in contrast to existing literature data. Nonetheless, the observation is consistent with our prior studies that the fasting glucose levels of control rats typically fell within 170~220 mg/dL range [ 30 , 31 , 46 ]. Moreover, the HOMA-IR value in DF group was slightly lower than in the DM group, however, there was no significant difference between the two groups, which was likely due to the fact that the fasting insulin levels did no differ between DM and DF groups, as HOMA-IR is calculated based on the fasting blood glucose and insulin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Control rats were administered with saline injection and continued on a normal diet (NC group). The STZ-injected, high fat-fed rat model, with lower mortality rates compared to a single high dose of STZ injection model, provides a good animal model of T2DM that mimics insulin resistance syndrome and is suitable for evaluating the antidiabetic activity of test compound [ 31 , 34 ]. The composition of these diets and the fatty acid composition of fish oil were performed as previously described [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the study in C57BL/6 mice indicated that COS ameliorated hepatic oxidative stress by activating the nuclear factor E2-related factor 2 (Nrf2) pathway and upregulating gene expressions of antioxidant enzymes, including GSH peroxidase (GSH-Px), superoxide dismutase (SOD), NADPH quinone oxidoreductase 1 (NQO1), heme oxygenase-1 (HO-1), and glutathione S-transferase alpha 1 (GSTA1) [ 53 ]. The results from Liu et al showed that supplementation of COS increased superoxide dismutase activity and decreased lipid peroxidation products, which contributed to alleviating abnormal glucose metabolism in the HFD/streptozotocin-induced diabetic rat livers [ 54 ].…”
Section: Biological Activities Of Chitosan and Cosmentioning
confidence: 99%
“…Glucose metabolism is closely associated with lipid metabolism. Indeed, the anabolic and catabolic pathways involved in the metabolism of lipids and glucose in the liver are difficult to distinguish [ 33 ] and several links between glucose and lipid abnormalities have been recognized. [ 34 ] For example, hypertriglyceridemia is both a consequence and cause of disturbances in glucose metabolism, [ 34 ] and the fatty acid content of the diet influences glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%